Hemoperitoneum due to ruptured botryoid sarcoma of the uterus in young girl - Rajendran Ramaswamy; Elsayed Ali; Saif Saeed Ghalib; Ghazi Mukattash (Wolters Kluwer Medknow Publications, 2021)
Five-year-old girl presented with lower abdominal pain, pelvi-abdominal mass, and generalized abdominal tenderness. Ultrasound and computed tomography scans diagnosed heterogeneous pelvi-abdominal soft-tissue mass and a large amount of free peritoneal fluid. Laparotomy revealed hemoperitoneum and ruptured tumor at the posterior uterine wall. Histopathology report was botryoid rhabdomyosarcoma (BRMS). This case is unique due to ruptured BRMS of the uterus in early childhood, with no vaginal bleeding.